(untitled) (Archives of Criminology, 2025)
Research on human trafficking highlights that its victims can be exploited in many areas of the economy. Moreover, some victims of trafficking are also forced to commit a crime (e.g. drug smuggling), though the victims of this peculiar type of crime can also be found among those seeking refugee status or international protection. This article discusses a new way of transferring victims of human trafficking across borders and describes who these people are, how they were recruited and how they were transported from their country of origin to the transit countries and finally reaching Poland. The modus operandi and profile of the perpetrators are also discussed. The research also describes the process of identifying victims of human trafficking, attempting to determine how, when and by whom these people were identified. The research findings are based on the files of asylum seekers that were gathered between 2012 and 2020 by the Office for Foreigners in Poland (the institution responsible for providing asylum status in Poland).